2016 US lymphoid malignancy statistics by World Health Organization subtypes. (12th September 2016) - Teras, Lauren R.; DeSantis, Carol E.; Cerhan, James R.; Morton, Lindsay M.; Jemal, Ahmedin; Flowers, Christopher R.
ABSTRACT: Collectively, lymphoid neoplasms are the fourth most common cancer and the sixth leading cause of cancer death in the United States. The authors provide contemporary lymphoid neoplasm statistics by subtype based on the 2008 World Health Organization classifications, including the most current US incidence and survival data. Presented for the first time are estimates of the total numbers of US lymphoid neoplasm cases by subtype as well as a detailed evaluation of incidence and survival statistics. In 2016, 136, 960 new lymphoid neoplasms are expected. Overall lymphoma incidence rates have declined in recent years, but trends vary by subtype. Precursor lymphoid neoplasm incidence rates increased from 2001 to 2012, particularly for B‐cell neoplasms. Among the mature lymphoid neoplasms, the fastest increase was for plasma cell neoplasms. Rates also increased for mantle cell lymphoma (males), marginal zone lymphoma, hairy cell leukemia, and mycosis fungoides. Like incidence, survival for both mature T‐cell lymphomas and mature B‐cell lymphomas varied by subtype and by race. Patients with peripheral T‐cell lymphomas had among the worst 5‐year relative survival (36%‐56%, depending on race/sex), while those with mycosis fungoides had among the best survival (79%‐92%). For B‐cell lymphomas, 5‐year survival ranged from 83% to 91% for patients with marginal zone lymphoma and from 78% to 92% for those with hairy cell leukemia; but the rates were as low as 47% to 63% for patients with Burkitt lymphoma and 44% to 48% for those with plasma cell neoplasms. In general, black men had the lowest survival across lymphoid malignancy subtypes. These contemporary incidence and survival statistics are useful for developing management strategies for these cancers and can offer clues regarding their etiology.CA Cancer J Clin 2016;66:443–459. © 2016 American Cancer Society .